Preeclampsia Prevention Using Routine Versus Screening Test–Indicated Aspirin in Low-Risk Women: A Cost-Effectiveness Analysis. Issue 6 (December 2018) - Mone, Fionnuala; O'Mahony, James F.; Tyrrell, Ella; Mulcahy, Cecilia; McParland, Peter; Breathnach, Fionnuala; Morrison, John J.; Higgins, John; Daly, Sean; Cotter, Amanda; Hunter, Alyson; Dicker, Patrick; et al.
Abstract : The objective was to evaluate whether routine aspirin 75 mg is more cost-effective than the Fetal Medicine Foundation screen-and-treat approach for preeclampsia prevention in low-risk nulliparous women. A health economic decision analytical model was devised to estimate the discounted net health and cost outcomes of routine aspirin versus Fetal Medicine Foundation screening test–indicated aspirin for a cohort of 100 000 low-risk nulliparous women. Both strategies were compared with no intervention. A subanalysis also compared disaggregated components of the algorithm. The analysis used data from hospital administration, literature, and a randomized controlled trial. Sensitivity analyses assessed the impact of aspirin adherence, test cost, and accuracy on study results. Presumed rates of preeclampsia were 3.75% with no intervention versus 0.45% with aspirin use. Results found that routine aspirin was the preferred strategy, in terms of greater health gains and larger cost savings. It provided 163 quality-adjusted life-years relative to no intervention, whereas the screen-and-treat policy achieved 108 quality-adjusted life-years. Routine aspirin would result in an estimated cost saving of [Euro sign]14.9 million annually relative to no intervention, whereas screen-and-treat approach would result in a smaller cost saving of [Euro sign]3.1 million. When the analysis was extended to consider alternative screen-and-treat strategies, routine aspirin remained the optimally cost-effective approach. In conclusion, routine aspirin use in low-risk nulliparous women has a greater health gain and cost saving compared with both the Fetal Medicine Foundation and other screen-and-treat approaches. Abstract : Supplemental Digital Content is available in the text.